A method for preparing high-purity silicon carbide tile boats

By spray drying reduction of mixed nano-silicon carbide powder and graphene oxide, and the application of silica sol-gel binder, combined with specific sintering and etching processes, the problems of purity, density and mechanical properties of high-purity silicon carbide tile boats were solved, and silicon carbide tile boats with high-temperature stability and micron-level precision were prepared.

CN120817808BActive Publication Date: 2025-11-14CHANGCHUN CHANGGUANG FINE PORCELAIN COMPOSITE MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511312059.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-15
Publication Date
2025-11-14
Estimated Expiration
2045-09-15

AI Technical Summary

Technical Problem

Existing technologies struggle to balance purity, cost, density, and mechanical properties when preparing high-purity silicon carbide tile boats, and it is also difficult to achieve micron-level precision and ultra-clean surfaces for complex structures.

Method used

The mixture of nano-silicon carbide powder, graphene oxide dispersion, and silane coupling agent is spray-dried and then reduced. This mixture is then combined with a silica sol-gel binder and high-purity carbon nanotubes for vacuum mixing. Subsequently, it is sintered under a specific atmosphere and pressure. Finally, it is subjected to vacuum plasma etching to form a graphene coating layer to improve mixing uniformity and particle bonding.

Benefits of technology

It achieves high density, excellent thermal conductivity and high rigidity of high-purity silicon carbide tile boats, which meet the needs of high-temperature precision processing of semiconductors, and combines lightweight and high rigidity with strong thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This application relates to the field of semiconductor manufacturing technology, specifically disclosing a method for preparing a high-purity silicon carbide tile boat. The preparation method is as follows: (1) preparing graphene-coated silicon carbide powder; (2) preparing a sol-gel binder; (3) preparing a green blank; (4) preparing a sintered green body; (5) placing the sintered green body in a vacuum plasma etching machine for etching to obtain a high-purity silicon carbide tile boat. The prepared high-purity silicon carbide tile boat has significant performance advantages, high specific stiffness, achieving a balance between lightweight and high rigidity, high thermal conductivity and excellent heat dissipation efficiency, high room temperature thermal expansion coefficient, outstanding thermal stability, and strong thermal shock resistance. It also features precision forming, high density, and high purity, making it suitable for high-temperature precision processing scenarios in semiconductors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of semiconductor manufacturing technology, and more specifically, it relates to a method for preparing high-purity silicon carbide tile boats. Background Technology

[0002] As a key component in high-temperature processing in fields such as semiconductors and photovoltaics, silicon carbide tile boats must possess high purity (metal impurities <1ppm), high-temperature stability, and precision structure. Their performance directly affects the manufacturing yield.

[0003] The existing technology has multiple bottlenecks: (1) In terms of raw material purification, although chemical vapor deposition can obtain high-purity powder, the cost is extremely high. Self-propagating high-temperature synthesis is prone to nitrogen exceeding the standard. Solid-state method is difficult to control magnetic impurities such as Fe and Al. It is difficult to balance purity and cost. (2) In terms of sintering process, pressureless sintering has high energy consumption and is prone to abnormal grain growth. Hot pressing sintering equipment has large investment and low efficiency. Liquid phase sintering reduces high-temperature performance due to additive residue. Reaction sintering has high porosity and insufficient strength. It is difficult to balance density and mechanical properties. (3) The forming process faces the contradiction between structural complexity and precision. Traditional methods are difficult to achieve micron-level precision and ultra-clean surface on complex load-bearing structures. With the development of wafer size and new battery technology, the requirements for the purity and high-temperature strength of tile boats have increased. The existing technology can no longer meet the needs. Based on the above statements, this application provides a method for preparing high-purity silicon carbide tile boats. The development of a preparation method that can balance purity, sintering and forming is of great significance for promoting the import substitution of semiconductor equipment materials in my country. Summary of the Invention

[0004] To address the technical problems mentioned in the background section, this application provides a method for preparing high-purity silicon carbide tile boats.

[0005] A method for preparing high-purity silicon carbide tile boats includes the following preparation steps:

[0006] (1) Mix nano silicon carbide powder, graphene oxide dispersion and silane coupling agent at a mass ratio of 100:30-35:2-3, stir at 60-70℃ for 1.5-2h, spray dry to obtain primary coated powder; place primary coated powder in hydrogen atmosphere and reduce for 2-3h to obtain graphene coated silicon carbide powder;

[0007] (2) Mix tetraethyl orthosilicate, ethanol and deionized water in a volume ratio of 1-3:2-5:0.5-0.6, adjust the pH to 3-4, and stir at 50-60℃ for 3-4 hours to form a silica sol; add polyvinylpyrrolidone and polyallylamine hydrochloride to the silica sol and continue stirring for 1-2 hours to obtain a sol-gel binder;

[0008] (3) Graphene-coated silicon carbide powder, high-purity carbon nanotubes, and sol-gel binder are mixed in a mass ratio of 100:5-6:8-10. After vacuum kneading, the mixture is placed into a tile boat mold. The pressure is first maintained at 100-150MPa for 5-8 minutes, and then increased to 250-300MPa at a rate of 50-60MPa / min. The pressure is maintained for 10-12 minutes to obtain the green blank.

[0009] (4) Place the green blank in a graphite furnace, first introduce nitrogen gas, heat to 1100-1200℃, hold for 40-60 min, then switch to argon gas, heat to 2100-2150℃ at 1-2℃ / min, hold for 3-4 h at 8-10MPa pressure, cool with the furnace to 500-600℃, introduce helium gas to accelerate cooling to room temperature, and obtain the sintered green body;

[0010] (5) Place the sintered blank in a vacuum plasma etching machine, introduce mixed gas, and etch for 30-40 minutes under the conditions of vacuum degree of 5-10 Pa and power of 300-400 W to obtain high-purity silicon carbide tile boat.

[0011] Preferably, the particle size of the nano silicon carbide powder in step (1) is 30-50 nm and the purity is ≥99.99%.

[0012] Preferably, the concentration of the graphene oxide dispersion in step (1) is 5-8 mg / mL.

[0013] Preferably, the reduction temperature of the primary coating powder in step (1) is 900-1000℃.

[0014] Preferably, in step (2), the mass of polyvinylpyrrolidone and polyallylamine hydrochloride accounts for 5-8% of the mass of the silica sol.

[0015] Preferably, in step (2), the mass ratio of polyvinylpyrrolidone to polyallylamine hydrochloride is 5-8:1-4.

[0016] Preferably, the purity of the high-purity carbon nanotubes in step (3) is ≥99.9%.

[0017] Preferably, in step (3), the vacuum degree of vacuum slurry is ≤0.1MPa and the vacuum slurry time is 40-50min.

[0018] Preferably, the pressure during the heating stage under nitrogen atmosphere in step (4) is 0.1-0.2 MPa, and the heating rate is 2-5 °C / min.

[0019] Preferably, the pressurization rate in step (4) under argon atmosphere is 0.5-1 MPa / min.

[0020] Preferably, the helium flow rate during the furnace cooling stage in step (4) is 15-20 L / min.

[0021] Preferably, the etching temperature in step (5) is 200-250℃.

[0022] Preferably, the mixed gas in step (5) consists of argon and hydrogen in a volume ratio of 3-5:1-2.

[0023] Preferably, the flow rate of the mixed gas in step (5) is 20-30 sccm.

[0024] In summary, this application has the following beneficial effects:

[0025] This application utilizes graphene oxide, which is uniformly adsorbed onto the surface of SiC through ultrasonic dispersion. After reduction with hydrogen, a graphene coating layer is formed. The two-dimensional sheet structure of graphene inhibits powder agglomeration and improves mixing uniformity. Furthermore, the high thermal conductivity and high strength of graphene can promote heat transfer and particle bonding during subsequent sintering, contributing to densification. By compounding polyvinylpyrrolidone (PVP) and polyallylamine hydrochloride, PPVP acts as a non-ionic dispersant, stabilizing the dispersion of SiC powder in the sol through steric hindrance, preventing sedimentation and stratification during molding, and ensuring uniform density of the green body. Polyallylamine hydrochloride, a cationic polyelectrolyte, forms hydrogen bonds and charge interactions with PPVP, synergistically enhancing the adhesion of the binder to SiC particles. Moreover, PPVP and polyallylamine hydrochloride are easily decomposed during sintering, avoiding impurity contamination and ensuring purity. Nitrogen gas is introduced at low temperatures to prevent SiC oxidation, while argon gas is switched at high temperatures. Argon has a larger atomic mass and is more stable at high temperatures, preventing N2 from reacting with SiC to form Si3N4 impurities. At the same time, argon's low thermal conductivity helps maintain temperature uniformity in the high-temperature zone, promoting particle rearrangement and densification. Helium's high thermal conductivity is used to achieve rapid cooling, suppress grain coarsening, and increase density. Detailed Implementation

[0026] The present application will be further described in detail below with reference to the embodiments.

[0027] The nano-silicon carbide powder (particle size: 50nm) used in the embodiments and comparative examples of this invention was purchased from Shandong Xinbaiyi Metal Materials Co., Ltd.; the graphene oxide was purchased from Changzhou Yaobang Friction Materials Factory; and the high-purity carbon nanotubes (purity: 99.99%) were purchased from Qinghe Ruijiang Metal Materials Co., Ltd.

[0028] Examples 1-3 provide a method for preparing high-purity silicon carbide tile boats.

[0029] Example 1

[0030] A method for preparing high-purity silicon carbide tile boats includes the following steps:

[0031] (1) Mix nano silicon carbide powder, graphene oxide dispersion and KH-560 at a mass ratio of 100:30:2, stir at 60℃ for 1.5h at a speed of 200rpm, and spray dry at 180℃ for 4h to obtain primary coated powder; place the primary coated powder in a hydrogen atmosphere and reduce at 900℃ for 2h to obtain graphene coated silicon carbide powder, wherein the concentration of graphene oxide dispersion is 5mg / mL;

[0032] (2) Tetraethyl orthosilicate, ethanol, and deionized water are mixed in a volume ratio of 1:2:0.5, the pH is adjusted to 3 with nitric acid, and stirred at 50°C and 100 rpm for 3 h to form a silica sol; polyvinylpyrrolidone and polyallylamine hydrochloride are added to the silica sol and stirred for another 1 h to obtain a sol-gel binder, wherein the mass of polyvinylpyrrolidone and polyallylamine hydrochloride accounts for 5% of the mass of the silica sol, and the mass ratio of polyvinylpyrrolidone and polyallylamine hydrochloride is 5:1;

[0033] (3) Graphene-coated silicon carbide powder, high-purity carbon nanotubes, and sol-gel binder are mixed in a mass ratio of 100:5:8. The mixture is then vacuum-kneaded for 40 min at a vacuum degree of 0.1 MPa. After vacuum kneading, the mixture is placed into a tile boat mold and first held at 100 MPa for 5 min. Then, the pressure is increased to 250 MPa at a rate of 50 MPa / min and held for 10 min to obtain a green blank.

[0034] (4) Place the green blank in a graphite furnace, first introduce nitrogen gas, heat to 1100℃ at 0.1MPa with a heating rate of 2℃ / min, hold for 40min, then switch to argon gas, heat to 2100℃ at 1℃ / min, and pressurize to 8MPa at a pressure rate of 0.5MPa / min, hold at 8MPa pressure for 3h, cool to 500℃ with the furnace, introduce helium gas to accelerate cooling to room temperature, helium gas flow rate is 15L / min, and obtain the sintered green body;

[0035] (5) The sintered blank is placed in a vacuum plasma etching machine, and a mixed gas is introduced. The flow rate of the mixed gas is 20 sccm. The etching is carried out for 30 min under the conditions of vacuum degree of 5 Pa and power of 300 W and etching temperature of 200℃ to obtain a high-purity silicon carbide tile boat. The mixed gas consists of argon and hydrogen in a volume ratio of 3:1.

[0036] Example 2

[0037] A method for preparing high-purity silicon carbide tile boats includes the following steps:

[0038] (1) Mix nano silicon carbide powder, graphene oxide dispersion and KH-560 at a mass ratio of 100:32:2.5, stir at 300 rpm for 1.8 h at 65 °C, and spray dry at 190 °C for 5 h to obtain primary coated powder; place the primary coated powder in a hydrogen atmosphere and reduce at 950 °C for 2.5 h to obtain graphene coated silicon carbide powder, wherein the concentration of graphene oxide dispersion is 7 mg / mL;

[0039] (2) Tetraethyl orthosilicate, ethanol, and deionized water were mixed in a volume ratio of 2:4:0.55, and the pH was adjusted to 3.5 with nitric acid. The mixture was stirred at 55°C and 200 rpm for 3.5 h to form a silica sol. Polyvinylpyrrolidone and polyallylamine hydrochloride were added to the silica sol and stirred for another 1.5 h to obtain a sol-gel binder. The mass of polyvinylpyrrolidone and polyallylamine hydrochloride accounted for 7% of the mass of the silica sol, and the mass ratio of polyvinylpyrrolidone to polyallylamine hydrochloride was 7:3.

[0040] (3) Graphene-coated silicon carbide powder, high-purity carbon nanotubes, and sol-gel binder are mixed at a mass ratio of 100:5.5:9. The mixture is vacuum-kneaded for 45 min at a vacuum degree of 0.1 MPa. After vacuum kneading, the mixture is placed into a tile boat mold and first held at a pressure of 125 MPa for 7 min. Then, the pressure is increased to 2580 MPa at a rate of 55 MPa / min and held for 11 min to obtain the green blank.

[0041] (4) Place the green blank in a graphite furnace, first introduce nitrogen gas, heat to 1150℃ at 0.15MPa with a heating rate of 4℃ / min, hold for 50min, then switch to argon gas, heat to 2125℃ at 1.5℃ / min, and pressurize to 9MPa at a pressure rate of 0.8MPa / min, hold at 9MPa pressure for 3.5h, cool to 550℃ with the furnace, introduce helium gas to accelerate cooling to room temperature, helium gas flow rate is 18L / min, and obtain the sintered green body;

[0042] (5) The sintered blank is placed in a vacuum plasma etching machine, and a mixed gas is introduced. The mixed gas flow rate is 30 sccm. The etching is carried out for 40 min under the conditions of vacuum degree of 10 Pa and power of 400 W and etching temperature of 230℃ to obtain a high-purity silicon carbide tile boat. The mixed gas is composed of argon and hydrogen with a volume ratio of 4:1.5.

[0043] Example 3

[0044] A method for preparing high-purity silicon carbide tile boats includes the following steps:

[0045] (1) Mix nano silicon carbide powder, graphene oxide dispersion and KH-560 at a mass ratio of 100:35:3, stir at 70°C for 2 hours at a speed of 400 rpm, and spray dry at 200°C for 6 hours to obtain primary coated powder; place the primary coated powder in a hydrogen atmosphere and reduce at 1000°C for 3 hours to obtain graphene-coated silicon carbide powder, wherein the concentration of graphene oxide dispersion is 8 mg / mL;

[0046] (2) Tetraethyl orthosilicate, ethanol, and deionized water were mixed in a volume ratio of 3:5:0.6, and the pH was adjusted to 4 with nitric acid. The mixture was stirred at 60°C and 300 rpm for 4 hours to form a silica sol. Polyvinylpyrrolidone and polyallylamine hydrochloride were added to the silica sol and stirred for another 2 hours to obtain a sol-gel binder. The mass of polyvinylpyrrolidone and polyallylamine hydrochloride accounted for 8% of the mass of the silica sol, and the mass ratio of polyvinylpyrrolidone to polyallylamine hydrochloride was 8:4.

[0047] (3) Graphene-coated silicon carbide powder, high-purity carbon nanotubes, and sol-gel binder are mixed in a mass ratio of 100:6:10. The mixture is then vacuum-kneaded for 50 min at a vacuum degree of 0.1 MPa. After vacuum kneading, the mixture is placed into a tile boat mold and first held at a pressure of 150 MPa for 8 min. Then, the pressure is increased to 300 MPa at a rate of 60 MPa / min and held for 12 min to obtain the green blank.

[0048] (4) Place the green blank in a graphite furnace, first introduce nitrogen gas, heat to 1200℃ at 0.2MPa with a heating rate of 5℃ / min, hold for 60min, then switch to argon gas, heat to 2150℃ at 2℃ / min, and pressurize to 10MPa at a pressure rate of 1MPa / min, hold at 10MPa pressure for 4h, cool to 600℃ with the furnace, introduce helium gas to accelerate cooling to room temperature, helium gas flow rate is 20L / min, and obtain the sintered green body;

[0049] (5) The sintered blank is placed in a vacuum plasma etching machine, and a mixed gas is introduced. The mixed gas flow rate is 30 sccm. The etching is carried out for 40 min under the conditions of vacuum degree of 10 Pa and power of 400 W and etching temperature of 250℃ to obtain a high-purity silicon carbide tile boat. The mixed gas consists of argon and hydrogen with a volume ratio of 5:2.

[0050] Comparative Example 1

[0051] A method for preparing high-purity silicon carbide tile boats includes the following steps:

[0052] (1) Mix nano silicon carbide powder and KH-560 at a mass ratio of 100:2, stir at 60°C for 1.5 h at a speed of 200 rpm, and spray dry at 180°C for 4 h to obtain primary coated powder; place the primary coated powder in a hydrogen atmosphere and reduce at 900°C for 2 h to obtain graphene-coated silicon carbide powder.

[0053] (2) Tetraethyl orthosilicate, ethanol, and deionized water are mixed in a volume ratio of 1:2:0.5, the pH is adjusted to 3 with nitric acid, and stirred at 50°C and 100 rpm for 3 h to form a silica sol; polyvinylpyrrolidone and polyallylamine hydrochloride are added to the silica sol and stirred for another 1 h to obtain a sol-gel binder, wherein the mass of polyvinylpyrrolidone and polyallylamine hydrochloride accounts for 5% of the mass of the silica sol, and the mass ratio of polyvinylpyrrolidone and polyallylamine hydrochloride is 5:1;

[0054] (3) Graphene-coated silicon carbide powder, high-purity carbon nanotubes, and sol-gel binder are mixed in a mass ratio of 100:5:8. The mixture is then vacuum-kneaded for 40 min at a vacuum degree of 0.1 MPa. After vacuum kneading, the mixture is placed into a tile boat mold and first held at 100 MPa for 5 min. Then, the pressure is increased to 250 MPa at a rate of 50 MPa / min and held for 10 min to obtain a green blank.

[0055] (4) Place the green blank in a graphite furnace, first introduce nitrogen gas, heat to 1100℃ at 0.1MPa with a heating rate of 2℃ / min, hold for 40min, then switch to argon gas, heat to 2100℃ at 1℃ / min, and pressurize to 8MPa at a pressure rate of 0.5MPa / min, hold at 8MPa pressure for 3h, cool to 500℃ with the furnace, introduce helium gas to accelerate cooling to room temperature, helium gas flow rate is 15L / min, and obtain the sintered green body;

[0056] (5) The sintered blank is placed in a vacuum plasma etching machine, and a mixed gas is introduced. The flow rate of the mixed gas is 20 sccm. The etching is carried out for 30 min under the conditions of vacuum degree of 5 Pa and power of 300 W and etching temperature of 200℃ to obtain a high-purity silicon carbide tile boat. The mixed gas consists of argon and hydrogen in a volume ratio of 3:1.

[0057] Comparative Example 2

[0058] A method for preparing high-purity silicon carbide tile boats includes the following steps:

[0059] (1) Mix nano silicon carbide powder, graphene oxide dispersion and KH-560 at a mass ratio of 100:30:2, stir at 60℃ for 1.5h at a speed of 200rpm, and spray dry at 180℃ for 4h to obtain primary coated powder; place the primary coated powder in a hydrogen atmosphere and reduce at 900℃ for 2h to obtain graphene coated silicon carbide powder, wherein the concentration of graphene oxide dispersion is 5mg / mL;

[0060] (2) Tetraethyl orthosilicate, ethanol, and deionized water were mixed in a volume ratio of 1:2:0.5, and the pH was adjusted to 3 with nitric acid. The mixture was stirred at 50°C and 100 rpm for 3 hours to form a silica sol. Polyallylamine hydrochloride was added to the silica sol and the mixture was stirred for another 1 hour to obtain a sol-gel binder. The mass of polyallylamine hydrochloride accounted for 5% of the mass of the silica sol.

[0061] (3) Graphene-coated silicon carbide powder, high-purity carbon nanotubes, and sol-gel binder are mixed in a mass ratio of 100:5:8. The mixture is then vacuum-kneaded for 40 min at a vacuum degree of 0.1 MPa. After vacuum kneading, the mixture is placed into a tile boat mold and first held at 100 MPa for 5 min. Then, the pressure is increased to 250 MPa at a rate of 50 MPa / min and held for 10 min to obtain a green blank.

[0062] (4) Place the green blank in a graphite furnace, first introduce nitrogen gas, heat to 1100℃ at 0.1MPa with a heating rate of 2℃ / min, hold for 40min, then switch to argon gas, heat to 2100℃ at 1℃ / min, and pressurize to 8MPa at a pressure rate of 0.5MPa / min, hold at 8MPa pressure for 3h, cool to 500℃ with the furnace, introduce helium gas to accelerate cooling to room temperature, helium gas flow rate is 15L / min, and obtain the sintered green body;

[0063] (5) The sintered blank is placed in a vacuum plasma etching machine, and a mixed gas is introduced. The flow rate of the mixed gas is 20 sccm. The etching is carried out for 30 min under the conditions of vacuum degree of 5 Pa and power of 300 W and etching temperature of 200℃ to obtain a high-purity silicon carbide tile boat. The mixed gas consists of argon and hydrogen in a volume ratio of 3:1.

[0064] Comparative Example 3

[0065] A method for preparing high-purity silicon carbide tile boats includes the following steps:

[0066] (1) Mix nano silicon carbide powder, graphene oxide dispersion and KH-560 at a mass ratio of 100:30:2, stir at 60℃ for 1.5h at a speed of 200rpm, and spray dry at 180℃ for 4h to obtain primary coated powder; place the primary coated powder in a hydrogen atmosphere and reduce at 900℃ for 2h to obtain graphene coated silicon carbide powder, wherein the concentration of graphene oxide dispersion is 5mg / mL;

[0067] (2) Tetraethyl orthosilicate, ethanol, and deionized water are mixed in a volume ratio of 1:2:0.5, the pH is adjusted to 3 with nitric acid, and the mixture is stirred at 50°C and 100 rpm for 3 hours to form a silica sol; polyvinylpyrrolidone is added to the silica sol and stirring is continued for 1 hour to obtain a sol-gel binder, wherein the mass of polyvinylpyrrolidone accounts for 5% of the mass of the silica sol;

[0068] (3) Graphene-coated silicon carbide powder, high-purity carbon nanotubes, and sol-gel binder are mixed in a mass ratio of 100:5:8. The mixture is then vacuum-kneaded for 40 min at a vacuum degree of 0.1 MPa. After vacuum kneading, the mixture is placed into a tile boat mold and first held at 100 MPa for 5 min. Then, the pressure is increased to 250 MPa at a rate of 50 MPa / min and held for 10 min to obtain a green blank.

[0069] (4) Place the green blank in a graphite furnace, first introduce nitrogen gas, heat to 1100℃ at 0.1MPa with a heating rate of 2℃ / min, hold for 40min, then switch to argon gas, heat to 2100℃ at 1℃ / min, and pressurize to 8MPa at a pressure rate of 0.5MPa / min, hold at 8MPa pressure for 3h, cool to 500℃ with the furnace, introduce helium gas to accelerate cooling to room temperature, helium gas flow rate is 15L / min, and obtain the sintered green body;

[0070] (5) The sintered blank is placed in a vacuum plasma etching machine, and a mixed gas is introduced. The flow rate of the mixed gas is 20 sccm. The etching is carried out for 30 min under the conditions of vacuum degree of 5 Pa and power of 300 W and etching temperature of 200℃ to obtain a high-purity silicon carbide tile boat. The mixed gas consists of argon and hydrogen in a volume ratio of 3:1.

[0071] Comparative Example 4

[0072] A method for preparing high-purity silicon carbide tile boats includes the following steps:

[0073] (1) Mix nano silicon carbide powder, graphene oxide dispersion and KH-560 at a mass ratio of 100:30:2, stir at 60℃ for 1.5h at a speed of 200rpm, and spray dry at 180℃ for 4h to obtain primary coated powder; place the primary coated powder in a hydrogen atmosphere and reduce at 900℃ for 2h to obtain graphene coated silicon carbide powder, wherein the concentration of graphene oxide dispersion is 5mg / mL;

[0074] (2) Tetraethyl orthosilicate, ethanol, and deionized water are mixed in a volume ratio of 1:2:0.5, the pH is adjusted to 3 with nitric acid, and stirred at 50°C and 100 rpm for 3 h to form a silica sol; polyvinylpyrrolidone and polyallylamine hydrochloride are added to the silica sol and stirred for another 1 h to obtain a sol-gel binder, wherein the mass of polyvinylpyrrolidone and polyallylamine hydrochloride accounts for 5% of the mass of the silica sol, and the mass ratio of polyvinylpyrrolidone and polyallylamine hydrochloride is 5:1;

[0075] (3) Graphene-coated silicon carbide powder, high-purity carbon nanotubes, and sol-gel binder are mixed in a mass ratio of 100:5:8. The mixture is then vacuum-kneaded for 40 min at a vacuum degree of 0.1 MPa. After vacuum kneading, the mixture is placed into a tile boat mold and first held at 100 MPa for 5 min. Then, the pressure is increased to 250 MPa at a rate of 50 MPa / min and held for 10 min to obtain a green blank.

[0076] (4) Place the green blank in a graphite furnace, first introduce nitrogen gas, heat to 1100℃ at 0.1MPa with a heating rate of 2℃ / min, hold for 40min, heat to 2100℃ at 1℃ / min, and pressurize to 8MPa at a pressure rate of 0.5MPa / min, hold at 8MPa pressure for 3h, cool to 500℃ with the furnace, introduce helium gas to accelerate cooling to room temperature, helium gas flow rate is 15L / min, and obtain the sintered green body;

[0077] (5) The sintered blank is placed in a vacuum plasma etching machine, and a mixed gas is introduced. The flow rate of the mixed gas is 20 sccm. The etching is carried out for 30 min under the conditions of vacuum degree of 5 Pa and power of 300 W and etching temperature of 200℃ to obtain a high-purity silicon carbide tile boat. The mixed gas consists of argon and hydrogen in a volume ratio of 3:1.

[0078] Comparative Example 5

[0079] A method for preparing high-purity silicon carbide tile boats includes the following steps:

[0080] (1) Mix nano silicon carbide powder, graphene oxide dispersion and KH-560 at a mass ratio of 100:30:2, stir at 60℃ for 1.5h at a speed of 200rpm, and spray dry at 180℃ for 4h to obtain primary coated powder; place the primary coated powder in a hydrogen atmosphere and reduce at 900℃ for 2h to obtain graphene coated silicon carbide powder, wherein the concentration of graphene oxide dispersion is 5mg / mL;

[0081] (2) Tetraethyl orthosilicate, ethanol, and deionized water are mixed in a volume ratio of 1:2:0.5, the pH is adjusted to 3 with nitric acid, and stirred at 50°C and 100 rpm for 3 h to form a silica sol; polyvinylpyrrolidone and polyallylamine hydrochloride are added to the silica sol and stirred for another 1 h to obtain a sol-gel binder, wherein the mass of polyvinylpyrrolidone and polyallylamine hydrochloride accounts for 5% of the mass of the silica sol, and the mass ratio of polyvinylpyrrolidone and polyallylamine hydrochloride is 5:1;

[0082] (3) Graphene-coated silicon carbide powder, high-purity carbon nanotubes, and sol-gel binder are mixed in a mass ratio of 100:5:8. The mixture is then vacuum-kneaded for 40 min at a vacuum degree of 0.1 MPa. After vacuum kneading, the mixture is placed into a tile boat mold and first held at 100 MPa for 5 min. Then, the pressure is increased to 250 MPa at a rate of 50 MPa / min and held for 10 min to obtain a green blank.

[0083] (4) Place the green blank in a graphite furnace, first introduce nitrogen gas, heat to 1100℃ at 0.1MPa with a heating rate of 2℃ / min, hold for 40min, then switch to argon gas, heat to 2100℃ at 1℃ / min, and pressurize to 8MPa at a pressure rate of 0.5MPa / min, hold at 8MPa pressure for 3h, cool to 500℃ with the furnace, and cool naturally to room temperature to obtain the sintered green body;

[0084] (5) The sintered blank is placed in a vacuum plasma etching machine, and a mixed gas is introduced. The flow rate of the mixed gas is 20 sccm. The etching is carried out for 30 min under the conditions of vacuum degree of 5 Pa and power of 300 W and etching temperature of 200℃ to obtain a high-purity silicon carbide tile boat. The mixed gas consists of argon and hydrogen in a volume ratio of 3:1.

[0085] Performance testing

[0086] The comprehensive performance of the high-purity silicon carbide tile boats prepared in Examples 1-3 and Comparative Examples 1-5 of this application is as follows:

[0087] Purity: determined by glow discharge mass spectrometry;

[0088] Density and porosity: Tested according to national standard GB / T25995-2010 "Test Method for Density and Apparent Porosity of Fine Ceramics";

[0089] Young's modulus; tested according to national standard GB / T23265-2009 "Test Method for Elastic Modulus of Fine Ceramics - Resonance Method";

[0090] Thermal conductivity: Tested in accordance with national standard GB / T22588-2008 "Measurement of thermal diffusivity or thermal conductivity by flash method";

[0091] Specific stiffness: obtained by dividing the Young's modulus of the sample by the sample density;

[0092] Coefficient of thermal expansion at room temperature; tested according to national standard GB / T16535-2008 "Test Method for Linear Thermal Expansion Coefficient of Fine Ceramics - Push Rod Method";

[0093] The test results are shown in Table 1 below.

[0094] Table 1 Performance parameters of the high-purity silicon carbide tile boats prepared in Examples 1-3 and Comparative Examples 1-5

[0095]

[0096] As shown in Table 1, the high-purity silicon carbide tile boat prepared in this application has significant performance advantages, including high specific stiffness, achieving a balance between lightweight and high rigidity; thermal conductivity ≥185W / (m・K), resulting in excellent heat dissipation efficiency; high room temperature thermal expansion coefficient, outstanding thermal stability, and strong thermal shock resistance; and the combination of precision molding, high density, and high purity, making it suitable for high-temperature precision semiconductor processing scenarios.

[0097] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A method for preparing high-purity silicon carbide tile boats, characterized in that, The preparation steps include the following: (1) Mix nano silicon carbide powder, graphene oxide dispersion and silane coupling agent, stir evenly and spray dry to obtain primary coated powder; place primary coated powder in hydrogen atmosphere and reduce for 2-3 hours to obtain graphene coated silicon carbide powder. (2) Mix tetraethyl orthosilicate, ethanol and deionized water, adjust the pH to 3-4, and stir at 50-60℃ for 3-4 hours to form silica sol; add polyvinylpyrrolidone and polyallylamine hydrochloride to silica sol, and continue stirring for 1-2 hours to obtain sol-gel binder. (3) Mix graphene-coated silicon carbide powder, high-purity carbon nanotubes, and sol-gel binder. After vacuum kneading, put the mixture into a tile boat mold. First, hold the pressure at 100-150MPa for 5-8 minutes, then increase the pressure to 250-300MPa at a rate of 50-60MPa / min and hold the pressure for 10-12 minutes to obtain the green blank. (4) Place the green blank in a graphite furnace, first introduce nitrogen gas, heat to 1100-1200℃, hold for 40-60 min, then switch to argon gas, heat to 2100-2150℃ at 1-2℃ / min, hold for 3-4 h at 8-10MPa pressure, cool with the furnace to 500-600℃, introduce helium gas to accelerate cooling to room temperature, and obtain the sintered green body; (5) Place the sintered blank in a vacuum plasma etching machine, introduce mixed gas, and etch for 30-40 minutes to obtain a high-purity silicon carbide tile boat.

2. The method for preparing high-purity silicon carbide tile boats according to claim 1, characterized in that, The reduction temperature of the primary coating powder in step (1) is 900-1000℃.

3. The method for preparing high-purity silicon carbide tile boats according to claim 1, characterized in that, In step (2), the mass of polyvinylpyrrolidone and polyallylamine hydrochloride accounts for 5-8% of the mass of the silica sol.

4. The method for preparing high-purity silicon carbide tile boats according to claim 1, characterized in that, In step (2), the mass ratio of polyvinylpyrrolidone to polyallylamine hydrochloride is 5-8:1-4.

5. The method for preparing high-purity silicon carbide tile boats according to claim 1, characterized in that, In step (3), the purity of the high-purity carbon nanotubes is ≥99.9%; the vacuum degree of the vacuum slurry is ≤0.1MPa, and the vacuum slurry time is 40-50min.

6. The method for preparing high-purity silicon carbide tile boats according to claim 1, characterized in that, In step (4), the pressure during the heating stage under nitrogen atmosphere is 0.1-0.2 MPa, and the heating rate is 2-5 °C / min.

7. The method for preparing high-purity silicon carbide tile boats according to claim 1, characterized in that, In step (4), the pressure increase rate under argon atmosphere is 0.5-1 MPa / min; the helium flow rate during the furnace cooling stage is 15-20 L / min.

8. The method for preparing high-purity silicon carbide tile boats according to claim 1, characterized in that, The etching temperature in step (5) is 200-250℃.

9. The method for preparing high-purity silicon carbide tile boats according to claim 1, characterized in that, In step (5), the mixed gas consists of argon and hydrogen in a volume ratio of 3-5:1-2; the flow rate of the mixed gas is 20-30 sccm.

Citation Information

Patent Citations

  • Preparation method of large-size silicon carbide ceramic boat

    CN117756544A

  • Boat support and manufacturing method thereof

    CN119751095A